2012
DOI: 10.1186/1471-2458-12-685
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving associated with selected cancer risk behaviors and screening utilization among women: cross-sectional results of the 2009 BRFSS

Abstract: BackgroundInformal caregiving is increasingly common as the U.S. population ages, and there is concern that caregivers are less likely than non-caregivers to practice health-promoting behaviors, including cancer screening. We examined caregiving effects on cancer risk behaviors and breast and cervical cancer screening in the 2009 Behavioral Risk Factor Surveillance System.MethodsWomen age ≥41 with data on breast and cervical cancer screening were included (weighted frequency 3,478,000 women). Cancer screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 14 publications
(43 reference statements)
6
45
0
Order By: Relevance
“…Although there are benefits to providing care, 24 caregivers are vulnerable to increased depression 5 and other health problems ,6,7 and reduced preventive health behaviors. 8,9 As a consequence, caregiving is associated with increased individual and societal healthcare costs. 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Although there are benefits to providing care, 24 caregivers are vulnerable to increased depression 5 and other health problems ,6,7 and reduced preventive health behaviors. 8,9 As a consequence, caregiving is associated with increased individual and societal healthcare costs. 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Studies from foreign countries (mostly the USA) show equivocal results regarding the association between caregiving and caregiver preventive health behavior . Burton et al reported the relationship between spousal caregiving and lifestyle health behavior using data from the Cardiovascular Health Study .…”
Section: Discussionmentioning
confidence: 99%
“…In countries other than Japan, the effect of informal caregiving on the caregiver's health has been of great interest . In addition, a few studies have examined the relationship between informal caregiving and preventive clinical services . In Japan, routine health check‐ups are quite prevalent; for example, employers must carry out health check‐ups for their employees annually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and reduced preventive health behaviors (Son et al. ; Reeves, Bacon, and Fredman ). As a consequence, caregiving is often associated with increased health care costs (Van Houtven, Wilson, and Clipp ; Schulz and Cook ) and may even lead to increased mortality (Schulz and Beach ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%